Arthroscopic anterior cruciate ligament reconstruction with meniscal repair: single-sitting versus multiple-staged-functional outcome analysis - Kunapareddy, Praveen T.; Kanagarla, Siva P.; Vutharkar, Nageswara R.; Reddy, Venu G. K.; Tallapudi, Arun M. (International Journal of Research in Orthopaedics, 2025)
Background: Anterior cruciate ligament (ACL) injuries are frequently associated with meniscal tears. Management can be performed either as a single sitting procedure (ACL reconstruction with concomitant meniscal repair) or in staged operations. The optimal strategy regarding functional recovery remains debated. The purpose of this study was to compare functional outcomes of single sitting versus multiple sitting arthroscopic ACL reconstruction with meniscal repair using peroneus longus tendon (PLT) autograft. Methods: A prospective comparative study was conducted on 30 patients aged 18–50 years with ACL rupture and repairable meniscal tears, treated between November 2023 and November 2025. Patients were divided into two groups: group A (n=15) underwent single sitting ACL reconstruction with meniscal repair, and group B (n=15) underwent staged procedures. Functional outcomes were assessed using the International Knee Documentation Committee (IKDC) score and Lysholm score at baseline and at 12 months. Results: All patients completed a minimum follow-up of 12 months. Both groups showed significant improvement from baseline. IKDC: 84.8±6.4 (group A) versus 82.1±6.8 (group B), p=0.21. Lysholm: 89.4±5.2 (group A) versus 86.7±5.6 (group B), p=0.19. Median time to return to sport was 7 months in group A and 9 months in group B. No graft re-ruptures were reported. Meniscal healing failure occurred in 1 patient (6.7%) in group A and 2 patients (13.3%) in group B. Conclusion: Single sitting arthroscopic ACL reconstruction with meniscal repair using peroneus longus tendon autograft provides functional outcomes comparable to multiple sitting procedures, with the added advantage of earlier return to sport. It is a safe and effective option in appropriately selected patients.